PENYULUHAN TENTANG ALUR PELAYANAN PUSKESMAS PADA PENGUNJUNG PUSKESMAS REJOSARI TAHUN 2021 - Bobi Handoko; Akmal darman Putra; Ani Riza Wati (LPPM Universitas Awal Bros, 2021)
According to Permenkes No. 43 of 2019 Puskesmas is a health service facility that organizes public health efforts and first-level individual health efforts, by prioritizing promotive and preventive efforts in their working areas. The Puskesmas Information System is an arrangement that provides information to assist the decision-making process in implementing the management of the Puskesmas to achieve the target of its activities. The method we use is lecture and question and answer discussion. The tools we use during the counseling are brochures and banners. The counseling will be held at the Rejosari Health Center on Wednesday, July 7, 2021. From 08.00 to 11.00 WIB. The counseling materials that will be provided include understanding the flow of the puskesmas, providing information related to the units in the puskesmas and directing the instructions for the service flow at the puskesmas. At the end of the process of counseling the service flow at the puskesmas, visitors and patients can understand the existing service flow.